Plan de mejora para una fábrica de plástico sobre la base de una evaluación energética y de métodos de trabajo - Córdova Guerra, María Auxiliadora (2010)
This work is performed at plastic processing factory located at Guayaquil. The factory’s facilities have a high electricity consumption generated by its unplanned growth. This study looks to develop a proposal to reduce energy consumption, by means of improvements for internal procedures. First, we identify the opportunities of improvements, presenting the relevant characteristics of the facilities, considering production, processes and electrical consumption factors. Such information is used to determine the energy indexes by production kilo. The tools used for this procedure were the energetic diagnosis (phase two), diagnosis by processes, FMEA, simple recovery time and return on investment. Different saving potentialities were identified: illumination at production and administration areas, power control for dryers, implementation of control sheets for molds changes and ventilation system. The savings determined if the proposal is to be implemented rise up to 16,615 USD, compared to an investment of 6,785 USD, which will be recovered in a 5 months period. The technical evaluation of the implementation determined that there existed no barrier to its accomplishment